Uncertainty Management in Acquisitions: What Scenario Analysis Could Offer - Sievänen, Valtteri (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
This study answers to How scenario analysis could help acquiring companies to reduce uncertainty in the acquisition process? It is due to the mismatch between academic world’s caveat emptor and business world’s eagerness to pursue acquisitions that motivated this study. Acquisitions are as popular as ever, thus, managing the uncertainty surrounding these transactions is relevant. This study creates a generic theoretical model with a strategy-level scope. Thus, the study does not discuss nor does it seek answers to operational issues related in both fields. This study is explorative and constructivist in nature. It discusses briefly the concepts and relatedness of risk and uncertainty and establishes a hierarchy between these two: Risks being a “sub-section” of uncertainty, although not with clear boundaries. Acquisition theory follows the process view that understands acquisitions as a process with various levels – some strategic, some operational. Scenario analysis is presented as tool for management to enrich their strategic discussion and understand their future options. The empirical data collection is done through interviewing. The results are reflected on literature on strategic management, scenario literature, and on a consultancy’s report picturing firm’s strategies in accordance with their acquisition processes. The study has an abductive approach as it tries to combine multiple views and generates discussion between literature review, interviews, the report, and second round of literature. The model suggests three propositions: First, at the strategic decision making level, when the decision whether or not to pursue an acquisition growth strategy has been made, it provides firms new data and enriches the strategic discussion. Second, when the acquisition strategy has been created, it can be applied as a tool to measure possible acquisition targets against the backdrop of the first set of scenarios. Third, due to the scenario analysis’ requirement to include people with various backgrounds and from multiple levels of the corporate hierarchy, it could help managers to avoid biases stemming from hubris.